Virtual reality-delivered skills-based therapy for chronic lower back pain: from proof-of-concept to FDA authorization to clinical implementation in-home and beyond - Maddox, Todd; Sackman, Josh; Stoudt, Matthew; Chibbaro, Michael; Judge, Emily; Rothery, Regan; Donini, Jesse; Maddox, Roselani; Darnall, Beth D. (Frontiers in Virtual Reality, 2025)
Chronic lower back pain (cLBP) is the most prevalent pain condition globally. Pain education and cognitive behavior therapy (CBT) are one of many recommended front-line treatments, but access is poor due to barriers such as few trained and available local therapists, health insurance limits, and burdens associated with travel and treatment time. Immersive therapeutics, such as virtual reality-delivered therapy, might provide an effective, low-risk, and accessible cLBP treatment. This manuscript describes the path followed to develop, obtain FDA-authorization for, and commercially launch a Virtual Reality-Delivered Skills-Based therapy for cLBP, called RelieVRx®. We detail the iterative path to design, develop and validate this immersive therapeutic medical device and the process followed to obtain FDA-authorization. We briefly summarize the results from over 30 publications that empirically test iterations of the VR-delivered therapy. Key lessons for translating innovation from the laboratory into the commercial market are identified, including commercial launch, reimbursement strategy, and clinical implementation in the home.Clinical Trial RegistrationClinicalTrials.gov, identifier NCT05263037.